Social Disconnectedness, Loneliness, and Mental Health Among Adolescents in Danish High Schools: A Nationwide Cross-Sectional Study - Santini, Ziggi Ivan; Pisinger, Veronica S. C.; Nielsen, Line; Madsen, Katrine Rich; Nelausen, Malene Kubstrup; Koyanagi, Ai; Koushede, Vibeke; Roffey, Sue; Thygesen, Lau C.; Meilstrup, Charlotte (Frontiers in Behavioral Neuroscience, 2021)
Background: Previous research has suggested that social disconnectedness experienced at school is linked to mental health problems, however, more research is needed to investigate 1) whether loneliness may partly explain such associations, and 2) how the accumulation of various types of social disconnectedness at school are associated with risk for mental health problems. Methods: Using data from the Danish National Youth Study 2019 (UNG19), nation-wide cross-sectional data from 29,086 high school students in Denmark were analyzed to assess associations between social disconnectedness experienced at school (lack of classmate support, lack of teacher support, lack of class social cohesion, and not being part of the school community) and various mental health outcomes, as well as the mediating role of loneliness for each type of disconnectedness. Multilevel regression analyses were conducted to assess the associations. Results: Descriptive analyses suggest that 27.5% of Danish high school students experience at least one form of social disconnectedness at school. Each type of social disconnectedness was positively associated with mental health problems (depression symptoms, anxiety symptoms, stress, sleep problems, suicidal ideation, non-suicidal self-injury, eating disorder, body dissatisfaction, and low self-esteem) and negatively associated with mental well-being. In all cases, loneliness significantly mediated the associations. We found a clear dose-response pattern, where each addition in types of social disconnectedness experienced at school was associated with 1) stronger negative coefficients with mental well-being and 2) stronger positive coefficients with mental health problems. Conclusion: Our results add to a large evidence-base suggesting that mental health problems among adolescents may be prevented by promoting social connectedness at school. However, focusing on single indicators of school social disconnectedness would appear to be insufficient. Fostering social connectedness at school may prevent loneliness, which in turn may promote mental well-being and prevent mental health problems during the developmental stages of adolescence. Implications for practices within school settings to enhance social connectedness are discussed.